Pertanggungjawaban Pidana atas Kejahatan Terhadap Kemanusiaan dalam Perspektif Hukum Pidana Internasional (Studi Kasus Penangkapan Presiden Hissène Habré ) - Salsabila, Syana Mifta; Putri, Syifadilla Subagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the concept of individual criminal responsibility for crimes against humanity within the framework of international criminal law as outlined in the Rome Statute of 1998. It also analyzes the application of this principle through the case of President Hissène Habré of Chad, which stands as a landmark in international justice. The study finds that crimes against humanity are grave offenses committed on a widespread and systematic scale, where perpetrators can be held accountable regardless of rank or political authority. The principle of individual criminal responsibility affirms that state officials, including heads of state, are not immune from prosecution for serious violations of human rights.